What's 'structural' about unemployment in Europe: On the Determinants of the European Commission's NAIRU Estimates - Jakob Kapeller; Philipp Heimberger; Bernhard Schütz (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2016)
This paper analyzes the determinants of the European Commission's NAIRU estimates for 14 European OECD countries during 1985-2012. The NAIRU is a poor proxy for 'structural unemployment': Labor market institutions - employment protection legislation, union density, tax wedge, minimum wages - underperform in explaining the NAIRU, while cyclical variables - capital accumulation and boom - bust patterns in housing markets - play an important role. This is relevant since the NAIRU is used to compute potential output and structural budget balances and, hence, has a direct impact on the scope and evaluation of fiscal policy in EU countries.
Keywords: C54; E24; E62; 330; NAIRU; potential output; fiscal policy coordination; unemployment in Europe; labor market flexibility